2019
DOI: 10.1007/s10853-019-03460-5
|View full text |Cite
|
Sign up to set email alerts
|

Superior ductility in magnesium alloy-based nanocomposites: the crucial role of texture induced by nanoparticles

Abstract: In an expansive field of metals, magnesium has been trending of late in automobile, aerospace, defense, sports, electronic and biomedical sectors as it offers an advantage in lightweighting. In the realm of Mg-based materials, Mg nanocomposites have a good combination of specific strength, thermal and damping properties, but lack a high ductility and do not typically undergo a large amount of uniform elongation. The current work bridges this gap by reporting a magnesium nanocomposite (Mg-1.8Y/1.5Y 2 O 3 ) that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 23 publications
0
10
2
Order By: Relevance
“…This is in contrary to the previously reported alloy nanocomposites, where marginal grain coarsening was observed when nanoparticles were added to magnesium-based alloys [14,21]. In previous works, it was reported that the nanoparticles, in certain magnesium matrices, alter the mechanism of dynamic recrystallization, from Zener pinning to localized particle stimulated nucleation, causing an inhomogeneity and; therefore, a bimodal grain size across the nanocomposite [14]. However, in this case, the nanoparticles aided the secondary phases in pinning the grain boundaries and refine the grains.…”
Section: Structural Characterizationcontrasting
confidence: 99%
See 2 more Smart Citations
“…This is in contrary to the previously reported alloy nanocomposites, where marginal grain coarsening was observed when nanoparticles were added to magnesium-based alloys [14,21]. In previous works, it was reported that the nanoparticles, in certain magnesium matrices, alter the mechanism of dynamic recrystallization, from Zener pinning to localized particle stimulated nucleation, causing an inhomogeneity and; therefore, a bimodal grain size across the nanocomposite [14]. However, in this case, the nanoparticles aided the secondary phases in pinning the grain boundaries and refine the grains.…”
Section: Structural Characterizationcontrasting
confidence: 99%
“…From the microstructural analysis of secondary phases, nanoparticles, and grain sizes, the results confirm that the nanoparticles contributed to the further grain refining of the material. This is in contrary to the previously reported alloy nanocomposites, where marginal grain coarsening was observed when nanoparticles were added to magnesium-based alloys [14,21]. In previous works, it was reported that the nanoparticles, in certain magnesium matrices, alter the mechanism of dynamic recrystallization, from Zener pinning to localized particle stimulated nucleation, causing an inhomogeneity and; therefore, a bimodal grain size across the nanocomposite [14].…”
Section: Structural Characterizationcontrasting
confidence: 74%
See 1 more Smart Citation
“…However, in the TID nanocomposite, a finer dispersion of Fe 3 O 4 nanoparticles was seen owing to the processing method which could have randomly scattered/broken the agglomeration of the nanoparticles during the turning process. The presence of the nanoparticles at the grain boundaries confirms the Zener pinning effects of the nanoparticles in the matrix during the dynamic recrystallization process (hot extrusion) [23,24]. This led to the reduction in the grain size due to the nanoparticles that assisted in pinning the grain boundaries, thereby increasing the grain boundary area, hindering grain growth and decreasing the grain size of the nanocomposites as compared to pure Mg. Coarsening of grain size with 3% Fe 3 O 4 nanoparticles could be due to the agglomeration of the nanoparticles that reduced their pinning effects considerably.…”
Section: General Microstructurementioning
confidence: 53%
“…Preferred orientation (texture) is a complex effect that bridges powder diffraction to single-crystal diffraction. In recent years in materials science there has been an increasing trend towards the synthesis and subsequent analysis of materials displaying only partial order, often in the nanometre length scale in the form of nanoparticles (Tekumalla et al, 2019), thin films (Rijckaert et al, 2018;Dippel et al, 2019), or fibretextured materials that are bone-like (Tan et al, 2019) or wood-like (Lagerwall et al, 2014). The analysis of these kinds of materials is best performed within the framework of the total scattering approach that prescinds from periodicity and therefore avoids Bragg formalism, yet provides quantitative information on the structural parameters as well as on the size and shape of the scattering domain .…”
Section: Introductionmentioning
confidence: 99%